Efektifitas Media Video Edukasi terhadap Peningkatan Pengetahuan Pasien dalam Perawatan Kaki Diabetes - Agustina Sabri; Elly L. Sjattar; Rosyidah Arafat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This review aims to systematically identify and analyze the effectiveness of educational video media in increasing patient knowledge in diabetic foot care. This research is a systematic review based on the PRISMA checklist. The study designs in this review are Pre-Experiment, Randomized Controlled Trial (RCT) and Quasi Experimental. Search for study articles using the PubMed, Science Direct, Willey, ProQuest, Garuda, Gray Literature and Coachrane Library databases. Article quality assessment was carried out using CASP, Cochran risk of bias and John Hopkins. The results of the research, of the six articles that have been included, four articles use a Randomized Controlled Trial (RCT) study design, one article uses a Quasi Experimental study design and one article uses a Pre-Experiment Conclusion study design, all research results show an increase in knowledge after being given education health videos about foot care. This is because video media is easy to use and can be played repeatedly by patients. Keywords: Diabetes Mellitus, Diabetic Foot Care, Knowledge, Educational Videos